Determinación del perfil metabolómico, fenoles totales y actividad antioxidante de la especie Physalis angulata - Huerta Guerra, Katerin Leidy (2024)
The present research explores the properties of P. angulata, a plant species from the Solanaceae family, recognized for its applications in traditional medicine to treat chronic diseases such as diabetes and cancer. The objective of this study was to determine the metabolomic profile, total phenolic content, and antioxidant activity in different organs of the plant. For this, samples of roots, stems, leaves, calyces, and fruits were collected from the Mohena Caño hamlet, Loreto region, Peru. A quantitative no experimental-analytical design was adopted, where ethanolic and aqueous extracts of each organ of the plant were analyzed using UHPLC-MS techniques and DPPH and ABTS assays. The results revealed the identification of 42 bioactive compounds, including withanolides and physalins. Regarding antioxidant activity, the ethanolic extracts showed superior performance to the aqueous ones, highlighting the ethanolic extract of the leaves for its high antioxidant capacity, which correlates with its total phenolic content. In conclusion, P. angulata is established as a promising source of natural antioxidants, especially the leaves, suggesting its potential use in the development of products aimed at the prevention of chronic-degenerative diseases. This finding highlights the importance of exploring native plants for the development of therapeutic alternatives in public health.